Disease duration before surgical resection for chronic pancreatitis impacts long-term outcome. Issue 44 (30th October 2020) - Willner, Antonie; Bogner, Andreas; Müssle, Benjamin; Teske, Christian; Hempel, Sebastian; Kahlert, Christoph; Distler, Marius; Weitz, Jürgen; Welsch, Thilo
Abstract : Abstract: Many patients with chronic pancreatitis (CP) undergo a step-up approach with interventional procedures as first-line treatment and resection reserved for later stages. The aim of this study was to identify predictive factors for a significant clinical improvement (SCI) after surgical treatment. All patients operated for CP between September 2012 and June 2017 at our center was retrospectively reviewed. A prospective patient survey was conducted to measure patients postoperative outcome. The primary endpoint SCI was defined as stable health status, positive weight development and complete pain relief without routine pain medication. Additionally, risk factors for relaparotomy were analyzed. A total of 89 patients with a median follow-up of 38 months were included. In most cases, a duodenum-preserving pancreatic head resection (n = 48) or pancreatoduodenectomy (n = 28) was performed. SCI was achieved in 65.3% (n = 47) of the patients after the final medium follow-up of 15.0 months (IQR: 7.0–35.0 months), respectively. Patients with a longer mean delay (7.7 vs 4 years) between diagnosis and surgical resection were less likely to achieve SCI ( P  = .02; OR .88; 95%CI .80–98). An endocrine insufficiency was a negative prognostic factor for SCI ( P  = .01; OR .15; 95%CI .04–68). In total, 96.2% of the patients had a complete or major postoperative relief with a mean pain intensity reduction from 8.1 to 1.9 on the visual analogue scale. The results support that surgical resection for CP should be considered at early stages. Resection can effectively reduce postoperative pain intensity and improve long-term success.